Effect of Display Resolution on Time to Diagnosis with Virtual Pathology Slides in a Systematic Search Task. - Randell, Rebecca; Ambepitiya, Thilina; Mello-Thoms, Claudia; Ruddle, Roy; Brettle, David; Thomas, Rhys; Treanor, Darren (Journal of Digital Imaging, 2015)
Performing diagnoses using virtual slides can take pathologists significantly longer than with glass slides, presenting a significant barrier to the use of virtual slides in routine practice. Given the benefits in pathology workflow efficiency and safety that virtual slides promise, it is important to understand reasons for this difference and identify opportunities for improvement. The effect of display resolution on time to diagnosis with virtual slides has not previously been explored. The aim of this study was to assess the effect of display resolution on time to diagnosis with virtual slides. Nine pathologists participated in a counterbalanced crossover study, viewing axillary lymph node slides on a microscope, a 23-in 2.3-megapixel single-screen display and a three-screen 11-megapixel display consisting of three 27-in displays. Time to diagnosis and time to first target were faster on the microscope than on the single and three-screen displays. There was no significant difference between the microscope and the three-screen display in time to first target, while the time taken on the single-screen display was significantly higher than that on the microscope. The results suggest that a digital pathology workstation with an increased number of pixels may make it easier to identify where cancer is located in the initial slide overview, enabling quick location of diagnostically relevant regions of interest. However, when a comprehensive, detailed search of a slide has to be made, increased resolution may not offer any additional benefit.